2022
DOI: 10.1186/s12877-022-03055-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between falls in elderly and the number of chronic diseases and health-related behaviors based on CHARLS 2018: health status as a mediating variable

Abstract: Objective Falling is one of the main causes of death and morbidity in the elderly. This study aims to explore the association between elderly patients with chronic diseases and their health-related behaviors and falls in the elderly, and to provide clues for the prevention and intervention of injuries caused by falls in the elderly. Methods Based on the basic demographic characteristics data, number of chronic diseases, health-related behaviors, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
1
11
0
1
Order By: Relevance
“…In fact, the number of health problems was identified in the multivariate analyses as an independent significant positive predictor of the risk of falling. The findings are in agreement with a recent study in China that examined the relation between the number of chronic diseases and falling in the elderly population ( 25 ).…”
Section: Discussionsupporting
confidence: 93%
“…In fact, the number of health problems was identified in the multivariate analyses as an independent significant positive predictor of the risk of falling. The findings are in agreement with a recent study in China that examined the relation between the number of chronic diseases and falling in the elderly population ( 25 ).…”
Section: Discussionsupporting
confidence: 93%
“…Factors related to falls include age, education level, family composition, residential area, economic activity, income level, alcohol consumption, smoking, physical activity, chronic disease, and BMI. In the elderly in the community, the incidence of falls is higher with increasing age [ 22 , 23 , 24 , 25 ]. Women have been found to have a higher risk of falls than men [ 21 , 22 ], and the unemployed and blue-collared workers with lower income are at a greater risk of falls [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of comparing the fall characteristics of the elderly in rural and urban areas, it has been confirmed that the lifetime fall history of the elderly in rural areas is greater than in urban areas [ 24 ]. The lower the educational level, the higher the risk of falls, and the higher the number of falls when living alone than when living with a spouse [ 21 , 23 , 25 ]. Drinking, smoking, physical activity, and chronic diseases are also associated with falls [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existe una asociación positiva entre un inadecuado estado nutricional y el riesgo de caídas (OR 1,8 IC95 %: 1,09 a 3,18) (4), situación que contribuye a la presencia de otras comorbilidades (5). Además, se ha identificado que la mortalidad debida a desnutrición proteico-ISSN: 0120-5498 • Med.…”
Section: Introductionunclassified